Research on the Influence Mechanism of Dual Leadership on the Constructive Deviant Behavior of the New Generation of Employees—The Chain Mediating Effect of Promoting Regulatory Focus and Role Width Self-Efficacy - Zhou, Yan; Qian, Huichi (Frontiers in Psychology, 2021)
Under the background of innovation to win, employees’ constructive deviant behavior has become an important way for organizations to break through the bottleneck of change and realize transformation and upgrading. At present, it has become the focus of academic and practical circles. Based on cognitive evaluation theory and social cognitive theory, this study explores the impact mechanism of dual leadership on employees’ constructive deviant behavior. Using hierarchical regression analysis and bootstrap method, this article empirically tests the questionnaire data of 333 new generation employees. It is found that dual leadership has a significant positive impact on constructive deviant behavior; role width, self-efficacy, and promoting regulatory focus play a complete intermediary role between dual leadership and constructive deviant behavior. Promoting regulatory focus and role width self-efficacy play a chain intermediary role in the action path of dual leadership on constructive deviant behavior. The research results enrich the theoretical framework of employees’ constructive deviant behavior from the perspective of leadership style, and provide a practical reference for leaders to effectively guide employees to make constructive deviant behavior.